POTRET PENGEMBANGAN DESA WISATA PINGE DALAM BINGKAI MEDIA SOSIAL INSTAGRAM DALAM PERSPEKTIF KOMUNIKASI PEMBANGUNAN - Putri Ekaresty Haes; Ni Nyoman Sri Wisudawati; Anak Agung Istri Agung Maheswari; Melati Budi Srikandi (LPSDI Bina Patria, 2025)
This qualitative research, using a case study approach, aims to analyse the role of Instagram as a development communication tool in the development of Pinge Tourism Village, Tabanan, Bali. The study's results reveal that Instagram serves as an adequate digital public space for promoting and branding Pinge Tourism Village. Community participation is essential for sustainable development in various sectors, including tourism and environmental management. Involving the local community will provide experience and ensure that economic benefits are distributed evenly. Through tags, geotags, and collaborations with influencers or other tourism accounts, Instagram helps Pinge Tourism Village build networks with external partners such as travel agencies, local governments, and tourism communities, thereby expanding the reach of its promotion. From a development communication perspective, Instagram facilitates a two-way communication process. Village managers can convey information while receiving feedback from visitors. This interaction aids in the planning and development of tourism villages that are more responsive to market needs and trends. However, the study also identified challenges, including pressure on village capacity and the potential for cultural commodification. The study concludes that, from a development communication perspective, Instagram functions as a strategic development communication tool that transforms local values into socioeconomic capital, while requiring critical and balanced content management to ensure genuine development sustainability. Furthermore, participatory development communication plays a vital role, with Instagram serving as a tool for this form of communication